2021
DOI: 10.1021/acs.jctc.1c00357
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Individual Hydrogen Bond Strengths in Ices via Periodic Local Vibrational Mode Theory: Beyond the Lattice Energy Picture

Abstract: Local stretching force constants derived from periodic local vibrational modes at the vdW-DF2 density functional level have been employed to quantify the intrinsic hydrogen bond strength of 16 ice polymorphs, ices Ih, II, III, IV, V, VI, VII, VIII, IX, XI, XII, XIII, XIV, XV, XVII, and XIX, that are stable under ambient to elevated pressures. Based on this characterization on 1820 hydrogen bonds, relationships between local stretching force constants and structural parameters such as hydrogen bond length and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 145 publications
(215 reference statements)
0
17
0
Order By: Relevance
“…114 Recently, more than 1,800 hydrogen bonds in 16 water ice polymorphs were investigated, and new relationships between hydrogen bond strength and local structural motifs were identified. 115 In this work, we provide three showcase examples to emphasize (1) the comparability of the local stretching force constant for the same type of chemical bonding across systems of different dimensions (from 0D to 3D), (2) the possibility of applying the local mode analysis in surfaces and interfaces, and (3) the microscopic dissection of the elasticity of materials in terms of chemical bonds and their local stretching force constants. The following discussion is complemented by a detailed description of all the computational methods used in each showcase example as presented in section 7.…”
Section: Showcase Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…114 Recently, more than 1,800 hydrogen bonds in 16 water ice polymorphs were investigated, and new relationships between hydrogen bond strength and local structural motifs were identified. 115 In this work, we provide three showcase examples to emphasize (1) the comparability of the local stretching force constant for the same type of chemical bonding across systems of different dimensions (from 0D to 3D), (2) the possibility of applying the local mode analysis in surfaces and interfaces, and (3) the microscopic dissection of the elasticity of materials in terms of chemical bonds and their local stretching force constants. The following discussion is complemented by a detailed description of all the computational methods used in each showcase example as presented in section 7.…”
Section: Showcase Examplesmentioning
confidence: 99%
“…In a theoretical study on molecular solids, we applied the local mode analysis to measure the intrinsic strength of the X–I···O type halogen bonds (X = I or Cl) and analyzed the underlying factors affecting the halogen bond strength . Recently, more than 1,800 hydrogen bonds in 16 water ice polymorphs were investigated, and new relationships between hydrogen bond strength and local structural motifs were identified …”
Section: Showcase Examplesmentioning
confidence: 99%
“…It is consistent with Nanayakkara's report. 29 The simulated and experimental data best match structure 4, and thus we present the simulated Raman scattering for structure 4 in Fig. 3.…”
Section: Resultsmentioning
confidence: 77%
“…The space group of ice given by Nanayakkara et al is Pbcn . 29 This paper reports our construction of possible conformations for ice XIX, our calculations of these conformations’ vibrational spectra, and our determination of the crystal structure of ice XIX from experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Finally we make a comment on a very recent theoretical study on the hydrogen-bond strengths in as many as 16 ice polymorphs including ice VI and I h by Kraka and co-workers. 37 They carried out density functional calculations to identify relationships between local stretch force constants of OH and hydrogen bonds and structural parameters such as hydrogenbond length and angle. They found that the hydrogen bond in ice I h is uniformly strong whereas that in ice VI has wide distribution in its strength, which is perfectly compatible with the present study.…”
Section: Resultsmentioning
confidence: 99%